The Veiled Muslim Woman as Subject in Contemporary Art: The Role of Location, Autobiography, and the Documentary Image - Behiery, Valerie (Implicit religion, 2013)
That the veil sign often operates to deny both veiled and unveiled Muslim women their status as subjects implies that references to veiled subjectivity propose an alternative vision. This article examines representations of the veil in contemporary art that displace Western mainstream perceptions by effectively portraying veiled Muslim women as subjects, therefore laying claim to the transformative capacity of selfhood and image. These representations are intimately linked to the phenomenon of globalization in that their recent visibility is due both to artists looking and working through another gaze/cultural screen and to a shift in the Western art apparatus that now exhibits their work. While they relate to other types of images of the veil in contemporary art in that they implicitly contextualize the veil and challenge the stereotypes surrounding it, they differ in that they are neither nostalgic nor contestatory. Rather, the art works discussed, relating to location, autobiography and the desire to document, are rooted in daily life and memory. Their pictorial language is not alien to Western visual culture, making their novel depictions of veiled women, and thus by extension their and the veil's diversity, more salient.